2017
DOI: 10.1371/journal.pcbi.1005417
|View full text |Cite
|
Sign up to set email alerts
|

Modelling T cell proliferation: Dynamics heterogeneity depending on cell differentiation, age, and genetic background

Abstract: Cell proliferation is the common characteristic of all biological systems. The immune system insures the maintenance of body integrity on the basis of a continuous production of diversified T lymphocytes in the thymus. This involves processes of proliferation, differentiation, selection, death and migration of lymphocytes to peripheral tissues, where proliferation also occurs upon antigen recognition. Quantification of cell proliferation dynamics requires specific experimental methods and mathematical modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…1(b)). This slow recovery of the CD4 SP cells is consistent with the lack of a proliferation capacity of the CD4 SP cells [13,35], which leads to a prolonged recovery. The CD4 SP dynamics can be reproduced by no proliferation and mTEC-dependent death and outflux that represent the negative selection of the SP cells by the mTECs (Fig.…”
Section: Dp and Cd4 Sp Thymocytes Incoherently Regulate Mtec Recoverysupporting
confidence: 73%
See 1 more Smart Citation
“…1(b)). This slow recovery of the CD4 SP cells is consistent with the lack of a proliferation capacity of the CD4 SP cells [13,35], which leads to a prolonged recovery. The CD4 SP dynamics can be reproduced by no proliferation and mTEC-dependent death and outflux that represent the negative selection of the SP cells by the mTECs (Fig.…”
Section: Dp and Cd4 Sp Thymocytes Incoherently Regulate Mtec Recoverysupporting
confidence: 73%
“…However, we have inconsistent evidences on the self-proliferation ability of the DP cells and its speed, which might depend on strains [35]; some of which showed that the DP cells proliferate little [22,36] whereas others suggest the DP cells can proliferate faster than the other types of the thymocytes [35,37]. Our model coordinates these properties by an auto-inhibitory regulation of the DP proliferation represented by the logistic term in Eq.1, which can realize a fast proliferation during the recovery period and its slowdown at the steady state.…”
Section: Dp Recovery Is Achieved By Temporal Up-regulation Of Prolifementioning
confidence: 91%
“…Additionally, the action of telomerase, which is up-regulated in dividing lymphocytes (47), may mean that most T cell death is independent of the Hayflick limit. Time since haematopoiesis will be related to the age of the individual subject, the association between age of the individual and T cell dynamics has recently been studied in mice (48).…”
Section: Discussionmentioning
confidence: 99%
“…Values were calculated assuming that 10 8 T-cells are introduced; however, delivery rates due to any other desired number or blood concentration of cells could be calculated by multiplying results by the ratio of the desired number to 10 8 or multiplying blood concentration by the total blood volume in the target species. Although models to predict expansion of a T-cell population have been studied in the past [9,30], it is difficult to quantify cellular proliferation in or fractional recirculation from a given tissue. However, a maximum rate of delivery due to anatomy can be estimated with greater confidence, thus proliferation was not considered.…”
Section: Discussionmentioning
confidence: 99%